Prevalence of Obesity in Iranian Children: Systematic Review and Meta-Analysis - Moloud Fakhri; Diana Sarokhani; Mandana Sarokhani; Ali Hasanpour Dehkordi; Leila Jouybari (Indian Journal of Medical Specialities)
Background of the Study: Childhood obesity, in addition to the likelihood of its continuation in adulthood, is associated with an increase in mortality and various diseases. Purpose of the Study: This meta-analytic study aimed at determining the prevalence of obesity among Iranian children. Methodology: Two researchers independently searched national and international databases using MeSH, Scopus, PubMed, Science Direct, Web of Science, Springer, Magiran, Iranmedex, SID, Medlib, and the Google Scholar search engine. The heterogeneity between studies was evaluated using the I2 index. Data were analyzed using STATA software. This study was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Results: Among 93 studies with a sample size of 3,845,768, the prevalence of obesity in Iranian children was 7% (girls 8% and boys 10%), and the prevalence of overweight was 12% (girls 17% and boys 15%). The incidence rate of obesity in children was 13% based on US centers for disease control and prevention (CDC) 2000 reference, 11% on international obesity task force (IOTF) reference, 9% on World Health Organization reference, 9% on Iranian reference, 5% on CDC reference, and 3% on national center for health statistics (NCHS) reference. Meta-regression diagram also showed that the prevalence of obesity in children was not dependent on sample size. However, the prevalence of obesity declined during the years 1999–2016, which was statistically significant. Conclusion: The prevalence of obesity in Iranian children was less than of their overweight. On the other hand, the prevalence of childhood obesity in girls was lower than that of boys, and the prevalence of child overweight among girls was higher than that of boys.